Smart Generation System of Personalized Advertising Copy and Its Application to Advertising Practice and Research. Issue 4 (8th August 2019) - Deng, Shasha; Tan, Chee-Wee; Wang, Weijun; Pan, Yu
Abstract : Artificial intelligence in programmatic advertising constitutes fertile grounds for marketing communication with tremendous opportunities. Yet, despite its touted benefits, contemporary implementations of programmatic advertising do not harness self-generative technologies so much so that different consumers are exposed to identical content. Consequently, we advance a smart generation system of personalized advertising copy (SGS-PAC) that can automatically personalize advertising content to align with the needs of individual consumers. Analytical results from a user experiment involving about 80 subjects underscore that personalized advertising copies generated by SGS-PAC can bolster click rate in online advertising platforms. Findings from this study bear significant implications for the application of artificial intelligence in online advertising.